THE ORIGIN OF THE KAHNUJ OPHIOLITIC COMPLEX, SE OF IRAN: CONSTRAINTS FROM WHOLE ROCK AND MINERAL CHEMISTRY OF THE BANDE-ZEYARAT GABBROIC COMPLEX - Arvin, Mohsen; Babaei, Abbed; Ghadami, Gholamreza; Dargahi, Sara; Ardekani, Alireza Shaker (Ofioliti, 2005)
The Upper Jurassic-Lower Cretaceous Kahnuj ophiolite complex, a part of Jazmurian ophiolitic belt, is situated in the southeastern part of Iran and represents a remnant of the Mesozoic Neotethyan Ocean. The oceanic lithospheric section of the Kahnuj ophiolite comprises from bottom to top: a plutonic unit (Bande-Zeyarat Complex); a diabase sheeted dyke unit; and a volcanic unit (Dare-Anar Complex). Although it is extensively faulted and fractured, the internal relationships have been preserved. The Bande-Zeyarat gabbroic complex consists of layered gabbroic cumulates and isotropic gabbros. The cumulate gabbro shows adcumulate, mesocumulate and orthocumulate textures and is represented exclusively by olivine gabbro, gabbro, melagabbro, leucogabbro, anorthosite, with minor troctolite, gabbronorite, pegmatoid and tectonic rafts of dunite. The cumulate gabbro is characterized by well-developed magmatic layering, defined by variation in mode /or size of plagioclase and mafic minerals, and by a tectonic foliation which is marked by preferred flattening of all mineral phases. These two structures for most parts are sub-parallel to each other. Rhythmic layering is also present. The isotropic gabbro consists of hypidiomorphic granular uralitized pyroxene gabbro and hornblende gabbro with minor ilmenite-rich gabbro, olivine gabbro, diorite and trondhjemite. They are the most fractionated part of the gabbros, plagioclase is more albite rich, clinopyroxene and olivine are more iron rich. The layered gabbro shows strong positive Eu anomalies, attributable to high modal abundances of plagioclase, whereas the isotropic gabbro with hornblende predominant over plagioclase does not have any Eu anomalies. The isotropic gabbros are crystallized from influxes of slightly different less magnesiferous parental melts. They are related to the cumulate gabbro by crystal fractionation and represent late differentiation products which formed as the rate of the magma influx slowed and finally ceased. Mineral assemblages, mineral chemistry (i.e., Fo67.8-78.54, low Mg# < 84.16 and high Si relative to tetrahedral Al in clinopyroxenes), crystallization order (olivine-plagioclase-clinopyroxene) and whole rock chemistry suggest that the Bande-Zeyarat gabbroic complex has been produced by low to moderate pressure crystal fractionation from a tholeiitic basaltic magma similar to MORB. These data indicate that the Kahnuj ophiolite complex may represent an oceanic basin developed in the Mesozoic between the Lut block of Central Iran and the Bajgan-Dur-Kan microcontinents.